A psicologia e a Bíblia no aconselhamento de Larry Crabb - Almeida, Loyde Gonçalves de (2010)
This research aims to clarify the method of biblical counseling by Larry Crabb from the point of view of psychology and the Bible to bring a careful integration. Achieving an approach solidly based on Bible Scriptures, using the tools of secular psychology without betraying the "Biblical premise". Which encourages belief in the inerrant Bible and the grace of Christ almighty, believing that there is a personal and infinite God that revealed themself purposely in the written word, the Bible, and personally in the living word, Jesus Christ. In Crabb's approach the "mistaken belief , produce negative feelings and behaviors that prevent us to provide the need of a relationship with the Sacred. The purpose of the theory is focused on correcting negative thoughts and to promote the appropriate thought to produce correct behaviors and feelings. The focus is on the thoughts. The feelings of resentment, guilt and anxiety are the focal point of the disorder produced. Therefore, the task of a biblical counselor is directed to comprehend and unveil people's basic personal needs defined as meaning. Moreover let them perceive that this meaning is only attained through the recognition of their own value and importance in Christ, which Crabb defines as security. His theory is advised to leaders because it involves a transformative approach, highlighting the faith in God and the appreciation of the Bible as the Word of God.